2016
DOI: 10.1080/02640414.2016.1211730
|View full text |Cite
|
Sign up to set email alerts
|

Identification of temporal factors related to shot performance for indoor recurve archery

Abstract: The purpose of this study was to investigate the temporal phases of the archery shot cycle that distinguish the arrows distance from centre, in an attempt to understand critical factors that affect performance. Fifteen archers of varying ability each performed 30 shots at 18m. Fourteen potential predictor variables were measured for statistical modeling by stepwise multiple linear regression.The results show that pre-shot time (pre-performance routine), release time

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
13
0
5
Order By: Relevance
“…Panahan adalah olahraga ketepatan sasaran, karena tujuannya menembak anak panah ke sasaran setepat mungkin (Landers et al, 2013). Pada praktiknya olahraga panahan merupakan cabang olahraga yang sangat memerlukan koordinasi, daya tahan, kelentukan, panjang tarikan, dan keseimbangan untuk membentuk teknik memanah yang baik (Callaway, Wiedlack, Heller, & Callaway, 2016;Keast & Elliott, 2008;Landers et al, 2013;Mucedola & Mucedola, 2018;Spratford & Campbell, 2017;Tan, Koh, & Kokkonen, 2016). Faktorfaktor tersebut haruslah ditunjang dengan latihan yang baik serta kondisi fisik yang prima dan tahan lama.…”
Section: Pendahuluanunclassified
“…Panahan adalah olahraga ketepatan sasaran, karena tujuannya menembak anak panah ke sasaran setepat mungkin (Landers et al, 2013). Pada praktiknya olahraga panahan merupakan cabang olahraga yang sangat memerlukan koordinasi, daya tahan, kelentukan, panjang tarikan, dan keseimbangan untuk membentuk teknik memanah yang baik (Callaway, Wiedlack, Heller, & Callaway, 2016;Keast & Elliott, 2008;Landers et al, 2013;Mucedola & Mucedola, 2018;Spratford & Campbell, 2017;Tan, Koh, & Kokkonen, 2016). Faktorfaktor tersebut haruslah ditunjang dengan latihan yang baik serta kondisi fisik yang prima dan tahan lama.…”
Section: Pendahuluanunclassified
“…The archers were instructed to try to hit the center of the target on each shot. Accuracy of the shot was marked according to the standard rules as 10, 9, 8, 7, 6, or 0, starting from the center (10) to the outer ring (6) or miss (0). The first 10 shots were used to accommodate the archers to the room and to the measurement equipment, and the final 90 shots were used for data analysis.…”
Section: Task and Measurementsmentioning
confidence: 99%
“…This process requires quasi-static control of posture and the upper limbs while withstanding considerable forces from the bow and string. Previous research in archery examined and identified multiple accuracy-related movement characteristics like muscle activity patterns of the forearm [1][2][3][4], releasing the arrow within the ST-phase of the cardiac cycle [5], timing of several key actions and phases [6], special skills related to specificity of the target distance [7], and postural control.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research in this sport can be directly relevant to athlete's performance during championship (24). Finally, using temporal pattern of the shot offers coaches and scientists a straightforward method of data collection and analysis to determine the effect over time (25).…”
Section: Justificationmentioning
confidence: 99%
“…Archery has been practiced for millennium, with the current earliest archaeological recordings dating back to 65.000 B.C. The role of archery has progressed from a necessity for survival and hunting through warfare, a recreational pastime, to become an Olympic sport (25).…”
Section: Literature Reviewmentioning
confidence: 99%